2018
DOI: 10.1111/1346-8138.14575
|View full text |Cite
|
Sign up to set email alerts
|

Topical efinaconazole: A promising therapeutic medication for tinea unguium

Abstract: We treated tinea unguium (onychomycosis caused by dermatophytes) patients with efinaconazole 10% solution. All patients with tinea unguium who tested positive for fungi in fingernails and toenails, regardless of age or severity, were eligible for the treatment. The number of patients was 106, consisting of 43 men and 63 women with a mean age of 66.7 years. The patients were treated with efinaconazole for a mean treatment duration of 38.1 weeks. Therapeutic efficacy was rated on a 5-point scale as follows: "cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Limited to severe cases, the treatment success rate was 36.3% at week 72, but considering the 47.5% mycological cure rate and changes in nail growth, further improvement can be expected by continuous application. Noguchi et al 6 also reported that efinaconazole was effective regardless of age, disease severity and clinical type when administrated alone in patients with onychomycosis, including severe cases, consistent with the conclusions in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Limited to severe cases, the treatment success rate was 36.3% at week 72, but considering the 47.5% mycological cure rate and changes in nail growth, further improvement can be expected by continuous application. Noguchi et al 6 also reported that efinaconazole was effective regardless of age, disease severity and clinical type when administrated alone in patients with onychomycosis, including severe cases, consistent with the conclusions in our study.…”
Section: Discussionsupporting
confidence: 92%
“…4,5 However, in clinical practise, EFCZ may be used in cases exceeding the study criteria, namely more severe cases with more than 50% clinical involvement or with long-term use for over 1 year. 6 Therefore, it is meaningful to obtain information on the efficacy and safety of EFCZ when used in severe cases or applied for over 48 weeks to provide findings for clinical medicine.…”
Section: Introductionmentioning
confidence: 99%
“…A phase 3 trial reported efficacy and cure rates of 94.4% (84/89) and 59.4% (60/101), respectively, and more severe conditions, including an older age (78.1 vs 58.4 years old) and larger affected areas (86.6% vs 54.5%), delayed the treatment effect. On investigating severe onychomycosis cases (66.7 years old, 77.6% affected area) with topical efinaconazole for 38.1 weeks (mean), the efficacy and cure rates were 65.4% (34/52) and 5.8% (3/52), respectively 11 . Taken together, these findings suggest that fosravuconazole should be more effective than topical efinaconazole therapy for severe onychomycosis.…”
Section: Discussionmentioning
confidence: 83%
“…The normal average toenail thickness is 1.65 ± 0.43 mm in men and 1.38 ± 0.20 mm in women 11 . The nail plate thickness changes with age 12 .…”
Section: Discussionmentioning
confidence: 96%
“…The complete cure rate at the final evaluation was 31.1%. 10 In another study, Noguchi et al 11 reported an efficacy rate of 65.4% in patients with an infected area exceeding 50%. In 2020, randomized controlled trials 7 , 12 of EFCZ with a high level of evidence were cited in the review of local treatment and device treatment for onychomycosis in the Cochrane Library.…”
Section: Discussionmentioning
confidence: 95%